Complex Feed-Forward and Feedback Mechanisms Underlie the Relationship Between Traumatic Brain Injury and the Gut–Microbiota–Brain Axis. Issue 3 (September 2019) - Patterson, T. Tyler; Nicholson, Susannah; Wallace, David; Hawryluk, Gregory W.J.; Grandhi, Ramesh
Abstract : ABSTRACT: Traumatic brain injury (TBI) contributes to nearly 1 in 3 injury-related deaths in the United States and accounts for a substantial public health burden and cost. The current literature reports that physiologic responses in the gastrointestinal system after TBI include, but are not limited to, epithelial barrier dysfunction, microbiota changes, and immunologic transformations. Recent evidence suggests gut alterations after TBI modify the homeostasis of the bidirectional gut–microbiota–brain axis, resulting in altered immune responses in the periphery and the brain. This cascade possibly contributes to impaired central nervous system (CNS) healing. Although attention to the gut–brain–microbiota axis has been increasing in the literature, the precise mechanisms underlying the changes observed after TBI remain unclear. The purpose of this review are to describe our current understanding regarding alterations to the gut–microbiota–brain axis after TBI, highlight the pathophysiologic changes involved, and evaluate how these variations modify healing in the CNS or even contribute to secondary injury. We also discuss current investigations into potential medical therapies directed at the gut–microbiota–brain axis, which might offer improved outcomes after TBI.